Music graduates and communities of practice - de Villiers, A.C. (South African Journal of Higher Education, 2019)
In this paper, I present a literature study that provides the theoretical framework for my discussion. The theoretical framework offers a discourse of the broad policy framework relating to higher education and includes analysis and reflection on policy that informs the Bachelor of Music degree. In the literature framework I also discuss research on the topic of graduate music qualifications and how these can inform practice. Curricula of the tertiary institutions that offer the Bachelor of Music degrees in South Africa do not appear to adequately consider future careers in their degree programmes. Alternatively, institutions have opted for vocational degrees in one field, namely the music industry, to the exclusion of other fields. In this paper I present a possible alternate way of approaching curriculum development so that module outcomes in music curricula are purposefully focused on future careers. By following this approach I contend that music graduates may be more employable, and be active members of communities of practice.